Harmonization with EU Customs Regulations (Acquis) on the Way to Accession: Prospects and Challenges for Ukraine - Oleh Kyryievskyi (Lex Portus, 2025)
This article examines the relationship between the ‘DCFTA acquis’ and the ‘accession acquis’ within customs law, with a specific focus on Ukraine’s compliance with these concepts. It analyzes recent legislative amendments, EU Commission reports, and other sources to identify potential challenges Ukraine and other candidate countries may face in implementing the accession acquis. In the first part, the article outlines the theoretical framework, highlighting the interconnectedness of the DCFTA and accession acquis. Despite differing scopes and requirements, both concepts are dynamic and flexible, allowing for simultaneous implementation. In the second part, the article assesses Ukraine’s progress in aligning its customs legislation with EU standards, highlighting discrepancies between the defined notion of the accession acquis and the actual situation. It underscores contradictions between the current external definition and the notion of flexibility. Finally, the article identifies key areas where challenges may arise in applying EU requirements and offers recommendations to address these issues, particularly concerning customs infringements and Authorized Economic Operators. It also discusses the implications of adopting a new customs code alongside ongoing EU reforms.